Pendugaan Umur Simpan Gula Kelapa Kristal dalam Kemasan Vakum menggunakan Metode Accelerated Shelf Life Test (ASLT) Model Arrhenius - Kavadya Syska; Nita Saniah Nuroniah; Ropiudin Ropiudin (Rona Teknik Pertanian, 2023)
Abstract Crystal coconut sugar contains reducing sugar in crystal coconut sugar which can cause crystal coconut sugar to be hygroscopic and make crystal coconut sugar easily absorb water. Efforts to slow down the rate of deterioration of crystal coconut sugar products can be done by packaging. Storage of crystal coconut sugar by vacuum packaging is an effort to inhibit the absorption of moisture from the environment so as to extend its shelf life. The aims of this study were 1) to examine the effect of storage and packaging temperature on several quality parameters of crystalline coconut sugar in vacuum packaging and 2) to develop the Arhenius Model Accelerated Shelf Life Test (ASLT) method to predict the shelf life of crystalline coconut sugar in vacuum packaging. This study used dried crystalline coconut sugar which was packaged using three different types of packaging, namely polyethylene (PE), vacuum packaging, and aluminum foil and then stored using different temperatures, namely 30°C and 15°C. then stored for 5 weeks and observed every 7 days. The results of calculations using the Arrhenius equation for the shelf life of crystalline coconut sugar with 2 storage temperatures and 3 different packages respectively, namely, PE packaging with a temperature of 30°C 1160 days and a temperature of 15°C 1697 days, vacuum packaging a temperature of 30°C 1504 days, temperature 15°C 2155 days, aluminum foil packaging temperature 30°C 7685 days and temperature 15°C 7690 days.